Ali predstojnik "dela dobro"? - Svedberg, Lars (Vodenje v vzgoji in izobraževanju, 2014)
A common finding of research into school performance is that it is the headteachers who are key actors. If headteachers are important - who is important for them? Thus the purpose of this paper is to provide knowledge about superintendent leadership. What outputs and outcomes are regarded as legitimate and meaningful and what impact does this new focus on performance measures have on the assignments for superintendents? The purpose of this paper is to describe and analyse superintendents% perceptions of what it means to do a 'good job'. Superintendents are understood as professionals who in everyday practice constantly interpret, negotiate, and manoeuvre in qualitatively different professional relationships. The empirical material consists of 40 short texts written by superintendents, while the structuring of the findings is inspired by social psychology. In the discussion it is argued that it is trust that represents the currency which is required to counterbalance the system%s uncertainties and incongruences.
Keywords: education; ethics; ethos; etika; headship; headteacher; management; menedžment; ravnatelji; vodenje; vzgoja in izobraževanje